Assessing differences in household needs: a comparison of approaches for the estimation of equivalence scales using German expenditure data - Christian Dudel; Jan Marvin Garbuszus; Julian Schmied (Empirical Economics, 2020)
Equivalence scales are routinely applied to adjust the income of households of different sizes and compositions. Because of their practical importance for the measurement of inequality and poverty, a large number of methods for the estimation of equivalence scales have been proposed. Until now, however, no comprehensive comparison of current methods has been conducted. In this paper, we employ German household expenditure data to estimate equivalence scales using several parametric, semiparametric, and nonparametric approaches. Using a single dataset, we find that some approaches yield more plausible results than others while implausible scales are mostly based on linear Engel curves. The results we consider plausible are close to the modified OECD scale, and to the square root scale for larger households.
Keywords: D12; I32; C14; C21; C31; 330; Equivalence scales; Household demand; Inequality measurement; Equivalence scale exactness; Engel curves; Independence of base